SPEECH ETIQUETTE FORMULAS IN UKRAINIAN BUSINESS COMMUNICATION: PERSPECTIVES OF FOREIGN LEARNERS - Borysova, Zoia; Borysova, Vira (Sworld-Us Conference proceedings, 2025)
Formulas of speech etiquette are an integral part of Ukrainian business communication, ensuring politeness, professionalism, and respect. For foreigners learning Ukrainian, mastering these formulas is challenging due to intercultural differences and lingu